AI's Influence On Financial Institutions: Exploring The Impact Of Artificial Intelligence In Finance (Journal of Namibian Studies : History Politics Culture, 2023)
Within the framework of India, this study investigates the revolutionary effects of AI on banking organizations. This paper analyses the impact of artificial intelligence (AI) on the Indian financial industry by reviewing relevant literature, case studies, and empirical data. The paper begins by outlining the major ways in which artificial intelligence is changing the financial sector. It then goes on to detail the ways in which Indian financial institutions are using AI in areas such as customer service, algorithmic trading, risk management, fraud detection, credit scoring, and regulatory compliance. It sheds light on the methods and results of using AI in India's financial ecosystem by citing case studies of prominent banks, fintech companies, and regulatory agencies.Additionally, the study examines the specific possibilities and threats linked to AI implementation in the Indian banking industry. It delves into the cultural aspects, existing regulations, data availability, talent acquisition, and regulatory frameworks that influence the use of artificial intelligence in Indian banks. Financial institutions in India may benefit from this study's insights into the consequences of AI adoption via the synthesis of empirical facts and theoretical frameworks. Taking into account the effects on stakeholders, market dynamics, and the regulatory landscape in the Indian context, it analyses the possible advantages, disadvantages, and social ramifications of AI-driven financial innovations.This study paper concludes with an in-depth analysis of how AI has affected India's banking sector. Policymakers, practitioners, and scholars may benefit from this analysis since it adds to the growing body of literature on technology-driven changes in India's financial industry by looking at AI adoption tactics, results, and obstacles.